2003
DOI: 10.4049/jimmunol.171.7.3705
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-10 in Susceptibility of BALB/c Mice to Infection with Leishmania mexicana and Leishmania amazonensis

Abstract: Recent studies have demonstrated the critical role of IL-10 in susceptibility to cutaneous and visceral leishmaniasis caused by Leishmania major and Leishmania donovani, respectively. To determine whether IL-10 also plays a similar role in the susceptibility and pathogenesis of cutaneous leishmaniasis caused by the New World species, L. mexicana and L. amazonensis, we analyzed their course of infection in IL-10-deficient BALB/c mice and their wild-type counterparts. Although IL-10-deficient mice infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 34 publications
4
63
2
1
Order By: Relevance
“…BALB/c mice deficient in IL-10 control L. major infection and harbor reduced parasite numbers (13), and IL-10-deficient C57BL/6 mice or C57BL/6 mice treated with anti-IL-10R Ab achieve sterile cure of L. major infection (28). In addition, we have shown that IL-10-deficient mice exhibit a dramatic increase in resistance to infection with Leishmania donovani and L. mexicana complex parasites (29,30). As is the case with IL-10, a number of studies have shown that neutralization of TGF-␤ promotes enhanced resistance to both cutaneous and visceral leishmaniasis (31,32).…”
Section: Discussionmentioning
confidence: 92%
“…BALB/c mice deficient in IL-10 control L. major infection and harbor reduced parasite numbers (13), and IL-10-deficient C57BL/6 mice or C57BL/6 mice treated with anti-IL-10R Ab achieve sterile cure of L. major infection (28). In addition, we have shown that IL-10-deficient mice exhibit a dramatic increase in resistance to infection with Leishmania donovani and L. mexicana complex parasites (29,30). As is the case with IL-10, a number of studies have shown that neutralization of TGF-␤ promotes enhanced resistance to both cutaneous and visceral leishmaniasis (31,32).…”
Section: Discussionmentioning
confidence: 92%
“…In mouse models of leishmaniasis, IL-10 secretion has been shown to be detrimental to infection with cutaneous strains such as L. major, Leishmania mexicana, and Leishmania amazonensis (6,7,(35)(36)(37), and to the visceral strain Leishmania donovani (38 -40). The dependence on IL-10 in determining disease outcome may also depend on the particular substrain of L. major, as has been documented with L. major LV39 (6) and L. major Seidman (35).…”
Section: Discussionmentioning
confidence: 99%
“…Both FccR and circulating IgG are needed for chronic disease, suggesting that ligation of FccR on macrophages by Leishmania-specific IgG triggers IL-10 production. IL-10 can act to inhibit nitric oxide synthesis, IL-12 and antigen presentation, and suppresses protective immunity [21,22].…”
Section: Introductionmentioning
confidence: 99%